Investigation of the Effects of Al2O3 Content and Cooling Rate on Crystallization in Fe2O3–CaO–Al2O3 System Using In Situ Confocal Laser Scanning Microscopy. Issue 7 (18th March 2019) - Park, Tae Jun; Choi, Joon Sung; Min, Dong Joon
Abstract : Sinter is a major Fe source, that is, used extensively in blast furnace processes worldwide. The chemical and physical properties of sinter are crucial factors that affect the operating stability of blast furnaces. The quality of sinter is largely determined by the phase fraction of the silico‐ferrite of calcium and aluminum (SFCA), which is a low‐melting‐point bonding phase formed during sintering. Calcium ferrite (CF)‐containing alumina is known to be the structural basis for SFCA and SFCA‐1, and provides basic information regarding the influence of Al2 O3 on the formation of CF solid solutions. In this work, experiments are conducted to investigate the crystallization behaviors of an Fe2 O3 –CaO–Al2 O3 system based on its Al2 O3 content and cooling rate. The effects of Al2 O3 additions are used to analyze changes in the phase formation temperature, phase ratio, and rate of decrease by using an in situ confocal laser‐scanning microscope, optical microscope, electron probe micro analyzer, and horizontal tube furnace. The temperatures at which the primary phase forms for various Al2 O3 contents and cooling rates differ from the equilibrium temperatures, and the phase‐formation temperature ranges vary with the cooling rate. Abstract : The crystallization behavior of an FeO3 –CaO–Al2 O3 system with various Al2 O3 contents is observed by using an in situ observation technique. The temperatures at which the primary phase forms for various Al2 O3 contents and cooling rates differ from the equilibrium temperatures, and the phase‐formation temperature ranges vary with the cooling rate.